Anharmoncity and low thermal conductivity in thermoelectrics. (March 2018) - Chang, Cheng; Zhao, Li-Dong
Abstract: The thermoelectric (TE) efficiency is evaluated by the material thermoelectric figure of merit ( ZT ), which can be usually improved by enhancing the electrical transport properties and/or reducing the thermal conductivity. Seeking the material with low thermal conductivity is crucial for thermoelectrics, which enable us simplify complex thermoelectric parameters and focus on the optimization of electrical transport properties alone. Here, we summarized the relationship between anharmonicity and low thermal conductivity in thermoelectrics. Several strategies which yield anharmonicity are also suggested, including lone pair electron, resonant bonding and rattling model. At last, some intuitive methods were proposed and summarized to evaluate the anharmonicity. Graphical abstract: image Highlights: The low thermal conductivity is strictly related to anharmonicity. The physical issues including lone pair electron, resonant bonding and rattling model yield anharmonicity. The intuitive methods to evaluate the anharmonicity are proposed and summarized.